2014
DOI: 10.1016/j.phrs.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of large-conductance calcium- and voltage-activated potassium channels in leptin-induced neuroprotection of N-methyl-d-aspartate-exposed cortical neurons

Abstract: In the present study, the neuroprotective effects of the adipokine leptin, and the molecular mechanism involved, have been studied in rat and mice cortical neurons exposed to N-methyl-D-Aspartate (NMDA) in vitro. In rat cortical neurons, leptin elicited neuroprotective effects against NMDA-induced cell death which were concentration-dependent (10–100 ng/ml) and largest when the adipokine was preincubated for 2 hours before the neurotoxic stimulus. In both rat and mouse cortical neurons, leptin-induced neuropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
(65 reference statements)
3
22
0
Order By: Relevance
“…As we have just reported, progesterone and some other hormones, such as leptin and 3,5,3'-triiodothyronine has been shown to have neuroprotective effects in several experimental acute brain injury models [15,45,46] Herein, we have showed that oral administration of 100 mg/kg body/weight of progesterone every 2 days, starting at PN7, significantly preserves photoreceptor cell number and decrease cell death in experimental RP model, rd1 mouse (Figures 1 and 2). While this treatment does not appear to inhibit the pathological course of the disease, it seems to slow down its progression.…”
Section: Discussionmentioning
confidence: 60%
“…As we have just reported, progesterone and some other hormones, such as leptin and 3,5,3'-triiodothyronine has been shown to have neuroprotective effects in several experimental acute brain injury models [15,45,46] Herein, we have showed that oral administration of 100 mg/kg body/weight of progesterone every 2 days, starting at PN7, significantly preserves photoreceptor cell number and decrease cell death in experimental RP model, rd1 mouse (Figures 1 and 2). While this treatment does not appear to inhibit the pathological course of the disease, it seems to slow down its progression.…”
Section: Discussionmentioning
confidence: 60%
“…For example, do we have a central leptin resistance in urban children before weight changes take place? If so, since leptin plays a key role in the developing brain (Steppan and Swick, 1999;Stieg et al, 2015;Farr et al, 2014;Bouret, 2010;Johnston et al, 2014;Pérez-González et al, 2011;Busch et al, 2011;Folch et al, 2012;Zhang et al, 2013;Mancini et al, 2014;Davis et al, 2014) are the high leptin concentrations in serum associated with high CSF leptin and low leptin receptors mRNA in target areas like hippocampus as in Alzheimer's patients? (Bonda et al, 2014a(Bonda et al, , 2014b.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ischemic cerebrovascular disease is the most common cerebrovascular disease and is a common cause of death and disability. According to several recent studies (Davis, Mudd, & Hawkins, ; Mancini et al, ; Valerio et al, ), leptin represents a potential therapy for ischemic cerebrovascular disease, providing another possibility for treating stroke.…”
Section: Introductionmentioning
confidence: 99%